Digital in-line X-ray holography with zone plates - Heine, Ruth; Gorniak, Thomas; Nisius, T.; Christophis, Christof; Pettitt, M. E.; Staier, Florian; Wilhein, T.; Rehbein, S.; Grunze, Michael; Rosenhahn, Axel (Ultramicroscopy, 2011)
Single pulse imaging with radiation provided by free-electron laser sources is a promising approach towards X-ray microscopy, which is expected to provide high resolution images of biological samples unaffected by radiation damage. One fully coherent imaging technique for this purpose is digital in-line holography. Key to its successful application is the creation of X-ray point sources with high photon flux. In this study we applied zone plates to create such point sources with synchrotron radiation provided by the storage ring BESSY II. The obtained, divergent light cone is applied to holographic microscopy of biological objects such as critical point dried Navicula perminuta diatoms and human cells using photons with an energy of 250eV. Compared to conventional experiments employing pinholes, exposure times are reduced by two orders of magnitude.